Upaya Guru dalam Mendukung Kesehatan Mental Siswa Kelas V SD Negeri 0510 Sihiuk Kabupaten Padang Lawas - Suci Laksana Lbs; Utari Utari (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study aimed to describe teachers' efforts in supporting the mental health of fifth-grade students at SD Negeri 0510 Sihiuk, Padang Lawas Regency. The study employed a qualitative approach with a descriptive qualitative design. The research subjects consisted of the fifth-grade teacher, the principal, and fifth-grade students. Data were collected through observation, interviews, and documentation, while data analysis used the Miles and Huberman model. The findings showed that students' mental health was generally in a fairly good category, as indicated by their ability to interact socially, collaborate with peers, and participate in learning activities. However, several students still demonstrated low self-confidence and difficulties in maintaining learning concentration. Teachers supported students' mental health by providing learning motivation, creating a comfortable learning environment, encouraging active participation, and building positive relationships with students. Although teachers faced challenges such as limited time and a large number of students, they continued to create a safe, comfortable, and supportive learning environment that fostered students' social and emotional development. Therefore, teachers play an important role in supporting students' mental health in elementary school settings.